First in situ observations of the goblin shark Mitsukurina owstoni - Aaron B. Judah; Alan J. Jamieson; Sarah R. D. Bingo; Megan E. Cundy; David A. Ebert; Steven Auscavitch; Harold K. Carlson; Tiffany Nicole G. Cunanan; Hayley B. Sims; Meagan Putts (Journal of Fish Biology, 2026)
We report the first live in situ observations of the iconic goblin shark ( Mitsukurina owstoni ) on a seamount near Jarvis Island in 2019 and on the slope of the Tonga Trench in 2024. Past observations are restricted to specimens hauled to the surface, resulting in limited knowledge of this species' ecology. These observations extend its known geographic and depth range considerably, and extend the depth range of lamniform sharks by 108 m. To further clarify habitat preferences and assess conservation status, further sampling, particularly with remote video, is required.

Molecular taxonomy of the guitarfish genus Acroteriobatus (Rhinopristiformes: Rhinobatidae) - Mia J. Groeneveld; Juliana D. Klein; Michaela van Staden; Rhett H. Bennett; Matthew L. Dicken; David A. Ebert; Bruce Q. Mann; Kashmika Perumal; Ralph G. A. Watson; Aletta E. Bester-van der Merwe (Marine Biodiversity, 2026)
Guitarfish species (genus Acroteriobatus ) display restricted distributions in undermanaged regions of intense fishing pressure. The importance of accurate specimen identification is well established, especially in the context of conservation management. However, guitarfishes remain poorly understood, which is exacerbated by taxonomic uncertainty due to morphological similarity. We therefore aimed (1) to identify molecular operational taxonomic units (MOTUs) within Acroteriobatus by analysing sampled specimens as well as publicly available sequence data for the cytochrome c oxidase subunit I ( COI ) and nicotinamide adenine dehydrogenase subunit 2 (ND2 ) genes, and (2) to augment and review the representation of these sequences on public databases. A molecular taxonomic approach integrating species delimitation and specimen assignment methods revealed 14 MOTUs. These MOTUs aligned with current species descriptions, displaying no evidence of cryptic diversity. Both genes demonstrated similar interspecific relationships that broadly reflected current distribution ranges, underscoring sub-regional endemism. Moreover, discrepancies in public sequence repositories were identified, attributed to misidentified specimens and the usage of outdated taxonomic nomenclature. Genetic diversity indices were substantially inflated when specimens were grouped based on reported species versus delimited MOTUs, thus overestimating genetic diversity. We highlight the need for extensive, curated DNA reference libraries, including revising earlier sequence entries in light of new taxonomic insights, to enable reliable identification of morphologically conserved species. The molecular resolution illustrated in this study can aid in clarifying taxonomic uncertainties in the genus Acroteriobatus .

Chemical recycling of refrigerator plastic waste by pyrolysis: Yields, product composition, and potential applications - Jonas Vogt; Axel D. Renno; Margret Fuchs; Tim Kurtz; Niklas Netsch; Frank Richter; Grazyna Straczewski; Britta Bergfeldt; Yuleika Carolina Madriz-Diaz; Andréa de Lima Ribeiro; Doreen Ebert; Salar Tavakkol; et al. (Fuel, 2025)

Strong Bottlenecks Constrain Adaptive Coevolution in a Host–Parasite Metapopulation - Pascal Angst; Christoph R. Haag; Frida Ben‐Ami; Peter D. Fields; Dieter Ebert (Molecular Ecology, 2025)
Although parasites are well‐known for adaptively evolving in order to exploit their hosts, they may experience strong genetic drift during transmission bottlenecks when infecting a new host. Host population structure and host population bottlenecks can also lead to genetic drift effects in parasite populations, constraining their adaptive evolution further. Here, we investigate the role of host population structure on the evolution of the microsporidian parasite Hamiltosporidium tvaerminnensis in a dynamic metapopulation of its microcrustacean host Daphnia magna . In following whole‐genome allele frequencies of 59 host and parasite subpopulations for up to 10 years, we found that both antagonists showed patterns of co‐dispersal and isolation‐by‐distance, but allele frequencies were much more dynamic in the host, where we found signatures of recurrent genetic bottlenecks. In the parasite, we observed high levels of shared heterozygosity among subpopulations but also subpopulation‐specific runs of homozygosity (ROHs). We hypothesise that deleterious ROHs, which originate from loss of heterozygosity events during asexual recombination, are fixed in subpopulations following host‐mediated parasite population bottlenecks when host and parasite co‐disperse into a habitat patch where the parasite is not yet present. Thus, host population structure and metapopulation dynamics leave a clearly traceable genomic signature in the coevolving parasite. Contrary to the prevailing assumption that parasites evolve at higher rates than their hosts, our study not only suggests that parasites can evolve more slowly than their host, but also that host dynamics can accelerate drift processes in the parasite.

Resistance exercise training in older men reduces ATF4-activated and senescence-associated mRNAs in skeletal muscle - Zachary D. Von Ruff; Matthew J. Miller; Tatiana Moro; Paul T. Reidy; Scott M. Ebert; Elena Volpi; Christopher M. Adams; Blake B. Rasmussen (GeroScience, 2025)
Sarcopenia increases the risk of frailty, morbidity, and mortality in older adults. Resistance exercise training improves muscle size and function; however, the response to exercise training is variable in older adults. The objective of our study was to determine both the age-independent and age-dependent changes to the transcriptome following progressive resistance exercise training. Skeletal muscle biopsies were obtained before and after 12 weeks of resistance exercise training in 8 young (24 ± 3.3 years) and 10 older (72 ± 4.9 years) men. RNA was extracted from each biopsy and prepared for analysis via RNA sequencing. We performed differential mRNA expression, gene ontology, and gene set enrichment analyses. We report that when comparing post-training vs pre-training 226 mRNAs and 959 mRNAs were differentially expressed in the skeletal muscle of young and older men, respectively. Additionally, 94 mRNAs increased, and 17 mRNAs decreased in both young and old, indicating limited overlap in response to resistance exercise training. Furthermore, the differential gene expression was larger in older skeletal muscle. Finally, we report three novel findings: 1) resistance exercise training decreased the abundance of ATF4-activated and senescence-associated skeletal muscle mRNAs in older men; 2) resistance exercise-induced increases in lean mass correlate with increased mRNAs encoding mitochondrial proteins; and 3) increases in muscle strength following resistance exercise positively correlate with increased mRNAs involved in translation, rRNA processing, and polyamine metabolism. We conclude that resistance exercise training elicits a differential gene expression response in young and old skeletal muscle, including reduced ATF-4 activated and senescence-associated gene expression.

Mechanistic in silico explorations of the immunogenic and synergistic effects of radiotherapy and immunotherapy: a critical review - Allison M. Ng; Kelly M. MacKinnon; Alistair A. Cook; Rebecca A. D’Alonzo; Pejman Rowshanfarzad; Anna K. Nowak; Suki Gill; Martin A. Ebert (Physical and Engineering Sciences in Medicine, 2024)
Immunotherapy is a rapidly evolving field, with many models attempting to describe its impact on the immune system, especially when paired with radiotherapy. Tumor response to this combination involves a complex spatiotemporal dynamic which makes either clinical or pre-clinical in vivo investigation across the resulting extensive solution space extremely difficult. In this review, several in silico models of the interaction between radiotherapy, immunotherapy, and the patient’s immune system are examined. The study included only mathematical models published in English that investigated the effects of radiotherapy on the immune system, or the effect of immuno-radiotherapy with immune checkpoint inhibitors. The findings indicate that treatment efficacy was predicted to improve when both radiotherapy and immunotherapy were administered, compared to radiotherapy or immunotherapy alone. However, the models do not agree on the optimal schedule and fractionation of radiotherapy and immunotherapy. This corresponds to relevant clinical trials, which report an improved treatment efficacy with combination therapy, however, the optimal scheduling varies between clinical trials. This discrepancy between the models can be attributed to the variation in model approach and the specific cancer types modeled, making the determination of the optimum general treatment schedule and model challenging. Further research needs to be conducted with similar data sets to evaluate the best model and treatment schedule for a specific cancer type and stage.

First record of the rare deep-sea shark, Scymnodon ichiharai Yano and Tanaka, 1984 (Squaliformes: Somniosidae) from Andaman Waters, India - Ravi Ranjan Kumar; S. Venu; K. K. Bineesh; K. A. Sajeela; D. A. Ebert; A. Gopalakrishnan; V. S. Basheer (Thalassas: An International Journal of Marine Sciences, 2024)

A novel SARS-CoV-2 modified live vaccine with an optimized safety profile induces sterile immunity in Syrian hamsters - A. Breithaupt; T. Britzke; J. Schön; G.T. Barut; N.J. Halwe; L. Ulrich; N. Ebert; B. Trüeb; M. Brügger; V. Thiel; M. Beer; D. Hoffmann (Journal of Comparative Pathology, 2024)

Quantitative 3D characterization of chromite ore particles - Jose Ricardo Assuncao Godinho; Shuvam Gupta; Camila Guimaraes da Silva Tochtrop; Raissa Demanou Tekeng; Matthew Hicks; Doreen Ebert; Jaakko Ihanus; Antti Roine; Jussi Liipo; Axel D. Renno (Minerals Engineering, 2023)

Significance of temperature as a key driver in ZVI PRB applications for PCE degradation - Adrian D. Metzgen; Andreas Dahmke; Markus Ebert (Journal of Contaminant Hydrology, 2023)

The transcription regulator ATF4 is a mediator of skeletal muscle aging - Matthew J. Miller; George R. Marcotte; Nathan Basisty; Cameron Wehrfritz; Zachary C. Ryan; Matthew D. Strub; Andrew T. McKeen; Jennifer I. Stern; Karl A. Nath; Blake B. Rasmussen; Andrew R. Judge; Birgit Schilling; et al. (GeroScience, 2023)
Aging slowly erodes skeletal muscle strength and mass, eventually leading to profound functional deficits and muscle atrophy. The molecular mechanisms of skeletal muscle aging are not well understood. To better understand mechanisms of muscle aging, we investigated the potential role of ATF4, a transcription regulatory protein that can rapidly promote skeletal muscle atrophy in young animals deprived of adequate nutrition or activity. To test the hypothesis that ATF4 may be involved in skeletal muscle aging, we studied fed and active muscle-specific ATF4 knockout mice (ATF4 mKO mice) at 6 months of age, when wild-type mice have achieved peak muscle mass and function, and at 22 months of age, when wild-type mice have begun to manifest age-related muscle atrophy and weakness. We found that 6-month-old ATF4 mKO mice develop normally and are phenotypically indistinguishable from 6-month-old littermate control mice. However, as ATF4 mKO mice become older, they exhibit significant protection from age-related declines in strength, muscle quality, exercise capacity, and muscle mass. Furthermore, ATF4 mKO muscles are protected from some of the transcriptional changes characteristic of normal muscle aging (repression of certain anabolic mRNAs and induction of certain senescence-associated mRNAs), and ATF4 mKO muscles exhibit altered turnover of several proteins with important roles in skeletal muscle structure and metabolism. Collectively, these data suggest ATF4 as an essential mediator of skeletal muscle aging and provide new insight into a degenerative process that impairs the health and quality of life of many older adults.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Demographic history shapes genomic variation in an intracellular parasite with a wide geographical distribution - Pascal Angst; Dieter Ebert; Peter D. Fields (Molecular Ecology, 2022)
Analysing variation in a species’ genomic diversity can provide insights into its historical demography, biogeography and population structure, and thus its ecology and evolution. Although such studies are rarely undertaken for parasites, they can be highly revealing because of the parasite's co‐evolutionary relationships with hosts. Modes of reproduction and transmission are thought to be strong determinants of genomic diversity for parasites and vary widely among microsporidia (fungal‐related intracellular parasites), which are known to have high intraspecific genetic diversity and interspecific variation in genome architecture. Here we explore genomic variation in the microsporidium Hamiltosporidium , a parasite of the freshwater crustacean Daphnia magna , looking especially at which factors contribute to nucleotide variation. Genomic samples from 18 Eurasian populations and a new, long‐read‐based reference genome were used to determine the roles that reproduction mode, transmission mode and geography play in determining population structure and demographic history. We demonstrate two main Hamiltosporidium tvaerminnensis lineages and a pattern of isolation‐by‐distance, but note an absence of congruence between these two parasite lineages and the two Eurasian host lineages. We suggest a comparatively recent parasite spread through Northern Eurasian host populations after a change from vertical to mixed‐mode transmission and the loss of sexual reproduction. While gaining knowledge about the ecology and evolution of this focal parasite, we also identify common features that shape variation in genomic diversity for many parasites, such as distinct modes of reproduction and the intertwining of host–parasite demographies.

Fast but steady: An integrated leaf‐stem‐root trait syndrome for woody forest invaders - Jason D. Fridley; Taryn L. Bauerle; Alaä Craddock; Alex R. Ebert; Douglas A. Frank; J. Mason Heberling; Elise D. Hinman; Insu Jo; Kelsey A. Martinez; Maria S. Smith; Lauren J. Woolhiser; Jingjing Yin (Ecology Letters, 2022)
Successful control and prevention of biological invasions depend on identifying traits of non‐native species that promote fitness advantages in competition with native species. Here, we show that, among 76 native and non‐native woody plants of deciduous forests of North America, invaders express a unique functional syndrome that combines high metabolic rate with robust leaves of longer lifespan and a greater duration of annual carbon gain, behaviours enabled by seasonally plastic xylem structure and rapid production of thin roots. This trait combination was absent in all native species examined and suggests the success of forest invaders is driven by a novel resource‐use strategy. Furthermore, two traits alone—annual leaf duration and nuclear DNA content—separated native and invasive species with 93% accuracy, supporting the use of functional traits in invader risk assessments. A trait syndrome reflecting both fast growth capacity and understorey persistence may be a key driver of forest invasions.

Evidence of historical isolation and genetic structuring among broadnose sevengill sharks (Notorynchus cepedianus) from the world’s major oceanic regions - Alicia C. J. Schmidt-Roach; Christine C. Bruels; Adam Barnett; Adam D. Miller; Craig D. H. Sherman; David A. Ebert; Sebastian Schmidt-Roach; Charlene da Silva; Christopher G. Wilke; Craig Thorburn; Jeffrey C. Mangel; Juan Manuel Ezcurra; et al. (Reviews in Fish Biology and Fisheries, 2021)

Friend or foe? The role of biotic agents in drought-induced plant mortality - Robert J. Griffin-Nolan; Neha Mohanbabu; Sarah Araldi-Brondolo; Alexander R. Ebert; Julie LeVonne; Joanna I. Lumbsden-Pinto; Hannah Roden; Jordan R. Stark; Jordon Tourville; Katie M. Becklin; John E. Drake; Douglas A. Frank; et al. (Plant Ecology, 2021)

Parasite‐mediated selection in a natural metapopulation of Daphnia magna - Andrea P. Cabalzar; Peter D. Fields; Yasuhiko Kato; Hajime Watanabe; Dieter Ebert (Molecular Ecology, 2019)
Parasite‐mediated selection varying across time and space in metapopulations is expected to result in host local adaptation and the maintenance of genetic diversity in disease‐related traits. However, nonadaptive processes like migration and extinction‐(re)colonization dynamics might interfere with adaptive evolution. Understanding how adaptive and nonadaptive processes interact to shape genetic variability in life‐history and disease‐related traits can provide important insights into their evolution in subdivided populations. Here we investigate signatures of spatially fluctuating, parasite‐mediated selection in a natural metapopulation of Daphnia magna . Host genotypes from infected and uninfected populations were genotyped at microsatellite markers, and phenotyped for life‐history and disease traits in common garden experiments. Combining phenotypic and genotypic data a Q ST – F ST ‐like analysis was conducted to test for signatures of parasite mediated selection. We observed high variation within and among populations for phenotypic traits, but neither an indication of host local adaptation nor a cost of resistance. Infected populations have a higher gene diversity ( H s) than uninfected populations and H s is strongly positively correlated with fitness. These results suggest a strong parasite effect on reducing population level inbreeding. We discuss how stochastic processes related to frequent extinction‐(re)colonization dynamics as well as host and parasite migration impede the evolution of resistance in the infected populations. We suggest that the genetic and phenotypic patterns of variation are a product of dynamic changes in the host gene pool caused by the interaction of colonization bottlenecks, inbreeding, immigration, hybrid vigor, rare host genotype advantage and parasitism. Our study highlights the effect of the parasite in ameliorating the negative fitness consequences caused by the high drift load in this metapopulation.

Dissecting the genetic architecture of a stepwise infection process - Matthew D. Hall; Jarkko Routtu; Dieter Ebert (Molecular Ecology, 2019)
How a host fights infection depends on an ordered sequence of steps, beginning with attempts to prevent a pathogen from establishing an infection, through to steps that mitigate a pathogen's control of host resources or minimize the damage caused during infection. Yet empirically characterizing the genetic basis of these steps remains challenging. Although each step is likely to have a unique genetic and environmental signature, and may therefore respond to selection in different ways, events that occur earlier in the infection process can mask or overwhelm the contributions of subsequent steps. In this study, we dissect the genetic architecture of a stepwise infection process using a quantitative trait locus (QTL) mapping approach. We control for variation at the first line of defence against a bacterial pathogen and expose downstream genetic variability related to the host's ability to mitigate the damage pathogens cause. In our model, the water‐flea Daphnia magna , we found a single major effect QTL, explaining 64% of the variance, that is linked to the host's ability to completely block pathogen entry by preventing their attachment to the host oesophagus; this is consistent with the detection of this locus in previous studies. In susceptible hosts allowing attachment, however, a further 23 QTLs, explaining between 5% and 16% of the variance, were mapped to traits related to the expression of disease. The general lack of pleiotropy and epistasis for traits related to the different stages of the infection process, together with the wide distribution of QTLs across the genome, highlights the modular nature of a host's defence portfolio, and the potential for each different step to evolve independently. We discuss how isolating the genetic basis of individual steps can help to resolve discussion over the genetic architecture of host resistance.

The genetic architecture underlying diapause termination in a planktonic crustacean - Till Czypionka; Peter D. Fields; Jarkko Routtu; Edwin van den Berg; Dieter Ebert; Luc De Meester (Molecular Ecology, 2019)
Diapause is a feature of the life cycle of many invertebrates by which unfavourable environmental conditions can be outlived. The seasonal timing of diapause allows organisms to adapt to seasonal changes in habitat suitability and thus is key to their fitness. In the planktonic crustacean Daphnia, various cues can induce the production of diapause stages that are resistant to heat, drought or freezing and contain one to two embryos in developmental arrest. Daphnia is a keystone species of many freshwater ecosystems, where it acts as the main link between phytoplankton and higher trophic levels. The correct seasonal timing of diapause termination is essential to maintain trophic interactions and is achieved via a genetically based interpretation of environmental cues like photoperiod and temperature. Field monitoring and modelling studies raised concerns on whether populations can advance their seasonal release from diapause to advances in spring phenology under global change, or if a failure to adapt will cause trophic mismatches negatively affecting ecosystem functioning. Our capacity to understand and predict the evolution of diapause timing requires information about the genetic architecture underlying this trait. In this study, we identified eight quantitative trait loci (QTLs) and four epistatic interactions that together explained 66.5% of the variation in diapause termination in Daphnia magna using QTL mapping. Our results suggest that the most significant QTL is modulating diapause termination dependent on photoperiod and is involved in three of the four detected epistatic interactions. Candidate genes at this QTL could be identified through the integration with genome data and included the presynaptic active zone protein bruchpilot . Our findings contribute to understanding the genomic control of seasonal diapause timing in an ecological relevant species.

Gene cluster conservation identifies melanin and perylenequinone biosynthesis pathways in multiple plant pathogenic fungi - Malaika K. Ebert; Rebecca E. Spanner; Ronnie de Jonge; David J. Smith; Jason Holthusen; Gary A. Secor; Bart P. H. J. Thomma; Melvin D. Bolton (Environmental Microbiology, 2019)
Summary Perylenequinones are a family of structurally related polyketide fungal toxins with nearly universal toxicity. These photosensitizing compounds absorb light energy which enables them to generate reactive oxygen species that damage host cells. This potent mechanism serves as an effective weapon for plant pathogens in disease or niche establishment. The sugar beet pathogen Cercospora beticola secretes the perylenequinone cercosporin during infection. We have shown recently that the cercosporin toxin biosynthesis ( CTB ) gene cluster is present in several other phytopathogenic fungi, prompting the search for biosynthetic gene clusters (BGCs) of structurally similar perylenequinones in other fungi. Here, we report the identification of the elsinochrome and phleichrome BGCs of Elsinoë fawcettii and Cladosporium phlei , respectively, based on gene cluster conservation with the CTB and hypocrellin BGCs. Furthermore, we show that previously reported BGCs for elsinochrome and phleichrome are involved in melanin production. Phylogenetic analysis of the corresponding melanin polyketide synthases (PKSs) and alignment of melanin BGCs revealed high conservation between the established and newly identified C. beticola , E. fawcettii and C. phlei melanin BGCs. Mutagenesis of the identified perylenequinone and melanin PKSs in C. beticola and E. fawcettii coupled with mass spectrometric metabolite analyses confirmed their roles in toxin and melanin production.

Spatial population genetic structure of a bacterial parasite in close coevolution with its host - Jason P. Andras; Peter D. Fields; Dieter Ebert (Molecular Ecology, 2018)
Knowledge of a species’ population genetic structure can provide insight into fundamental ecological and evolutionary processes including gene flow, genetic drift and adaptive evolution. Such inference is of particular importance for parasites, as an understanding of their population structure can illuminate epidemiological and coevolutionary dynamics. Here, we describe the population genetic structure of the bacterium Pasteuria ramosa , a parasite that infects planktonic crustaceans of the genus Daphnia . This system has become a model for investigations of host–parasite interactions and represents an example of coevolution via negative frequency‐dependent selection (aka “Red Queen” dynamics). To sample P. ramosa , we experimentally infected a panel of Daphnia hosts with natural spore banks from the sediments of 25 ponds throughout much of the species range in Europe and western Asia. Using 12 polymorphic variable number tandem repeat loci ( VNTR loci), we identified substantial genetic diversity, both within and among localities, that was structured geographically among ponds. Genetic diversity was also structured among host genotypes within ponds, although this pattern varied by locality, with P. ramosa at some localities partitioned into distinct host‐specific lineages, and other localities where recombination had shuffled genetic variation among different infection phenotypes. Across the sample range, there was a pattern of isolation by distance, and principal components analysis coupled with Procrustes rotation identified congruence between patterns of genetic variation and geography. Our findings support the hypothesis that Pasteuria is an endemic parasite coevolving closely with its host. These results provide important context for previous studies of this model system and inform hypotheses for future research.

Size, growth, and density data for shallow‐water sea urchins from Mexico to the Aleutian Islands, Alaska, 1956–2016 - Thomas A. Ebert; Louis M. Barr; James L. Bodkin; Dirk Burcham; Dominique Bureau; Henry S. Carson; Nancy L. Caruso; Jennifer E. Caselle; Jeremy T. Claisse; Sabrina Clemente; Kathryn Davis; Paul M. Detwiler; et al. (Ecology, 2018)
Size, growth, and density have been studied for North American Pacific coast sea urchins Strongylocentrotus purpuratus , S. droebachiensis, S. polyacanthus , Mesocentrotus (Strongylocentrotus) franciscanus , Lytechinus pictus , Centrostephanus coronatus , and Arbacia stellata by various workers at diverse sites and for varying lengths of time from 1956 to present. Numerous peer‐reviewed publications have used some of these data but some data have appeared only in graduate theses or the gray literature. There also are data that have never appeared outside original data sheets. Motivation for studies has included fisheries management and environmental monitoring of sewer and power plant outfalls as well as changes associated with disease epidemics. Studies also have focused on kelp restoration, community effects of sea otters, basic sea urchin biology, and monitoring. The data sets presented here are a historical record of size, density, and growth for a common group of marine invertebrates in intertidal and nearshore environments that can be used to test hypotheses concerning future changes associated with fisheries practices, shifts of predator distributions, climate and ecosystem changes, and ocean acidification along the Pacific Coast of North America and islands of the north Pacific. No copyright restrictions apply. Please credit this paper when using the data.

Squalus bassi sp. nov., a new long‐snouted spurdog (Chondrichthyes: Squaliformes: Squalidae) from the Agulhas Bank - S. T. de. F. L. Viana; M. R. de Carvalho; D. A. Ebert (Journal of Fish Biology, 2017)
The long‐snouted African spurdog Squalus bassi sp. nov. is described based on material collected from the outer shelf and upper continental slope off South Africa and Mozambique. Squalus bassi shares with S. mitsukurii, S. montalbani, S. chloroculus, S. grahami , S. griffini, S. edmundsi , S. quasimodo and S. lobularis a large snout with prenarial length greater than distance between nostrils and upper labial furrows, dermal denticles tricuspidate and rhomboid and elevated number of vertebrae. Squalus bassi can be distinguished from all its congeners by a combination of body and fin colouration, external morphometrics, vertebral counts and shape of dermal denticles. Similar long‐snouted congeners from the Indo‐Pacific region, including S. montalbani , S. edmundsi and S. lalannei are compared in detail with the new species. This new species has been misidentified as the Japanese S. mitsukurii and the Mediterranean S. blainvillei due to the lack of comparative morphological analyses. The validity of the nominal species S. mitsukurii in the south‐eastern Atlantic Ocean and western Indian Ocean is also clarified herein, indicating it has a more restricted geographical distribution in the North Pacific Ocean.

Color aberrations in Chondrichthyan fishes: first records in the genus Bathyraja (Chondrichthyes: Rajiformes: Arhynchobatidae) - J. S. Bigman; J. D. S. Knuckey; D. A. Ebert (Marine Biodiversity, 2016)

Effects of three novel resistant black raspberry selections on Amphorophora agathonica feeding behavior and performance - D. Lightle; M. Dossett; T. Ebert; C. E. Finn; R. R. Martin; J. C. Lee (Arthropod-Plant Interactions, 2015)

Genes mirror geography in Daphnia magna - Peter D. Fields; Céline Reisser; Marinela Dukić; Christoph R. Haag; Dieter Ebert (Molecular Ecology, 2015)
Identifying the presence and magnitude of population genetic structure remains a major consideration in evolutionary biology as doing so allows one to understand the demographic history of a species as well as make predictions of how the evolutionary process will proceed. Next‐generation sequencing methods allow us to reconsider previous ideas and conclusions concerning the distribution of genetic variation, and what this distribution implies about a given species evolutionary history. A previous phylogeographic study of the crustacean Daphnia magna suggested that, despite strong genetic differentiation among populations at a local scale, the species shows only moderate genetic structure across its European range, with a spatially patchy occurrence of individual lineages. We apply RAD sequencing to a sample of D. magna collected across a wide swath of the species' Eurasian range and analyse the data using principle component analysis ( PCA ) of genetic variation and Procrustes analytical approaches, to quantify spatial genetic structure. We find remarkable consistency between the first two PCA axes and the geographic coordinates of individual sampling points, suggesting that, on a continent‐wide scale, genetic differentiation is driven to a large extent by geographic distance. The observed pattern is consistent with unimpeded (i.e. no barriers, landscape or otherwise) migration at large spatial scales, despite the fragmented and patchy nature of favourable habitats at local scales. With high‐resolution genetic data similar patterns may be uncovered for other species with wide geographic distributions, allowing an increased understanding of how genetic drift and selection have shaped their evolutionary history.

Fusobacterium nucleatum associates with stages of colorectal neoplasia development, colorectal cancer and disease outcome - L. Flanagan; J. Schmid; M. Ebert; P. Soucek; T. Kunicka; V. Liska; J. Bruha; P. Neary; N. Dezeeuw; M. Tommasino; M. Jenab; J. H. M. Prehn; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2014)

Half a century (1954–2009) of dissection data of sea urchins from the North American Pacific coast (Mexico–Canada) - T. A. Ebert; J. C. Hernández; S. Clemente; M. P. Russell; L. V. Basch; R. A. Boolootian; P. M. Detwiler; M. C. Kenner; A. L. Lawrence; J. M. Lawrence; D. L. Leighton; J. S. Palleiro; et al. (Ecology, 2013)
Total body size, mass or linear measurements, and gonad mass or volumes have been recorded for the North American Pacific coast sea urchins Strongylocentrotus purpuratus, Mesocentrotus (Strongylocentrotus) franciscanus, and Lytechinus pictus by various workers at diverse sites and for varying lengths of time from 1954 to 2009. Some dissections included other body components such as the gut, body wall, and Aristotle's lantern, and some dissections included both wet and dry mass. There are numerous peer‐reviewed publications that have used some of these data, but some data have appeared only in graduate theses or in the gray literature. There also are data that have never appeared outside the original data sheets. Historically, data were used to describe reproductive cycles and then to compare responses to stressors such as food limitation or pollution. Differences in temperature among sites also have been explored. More recently, dissection data have linked gonad development to ocean conditions, so called bottom‐up forcing. The data set presented here is a historical record of gonad development for a common group of marine invertebrates in intertidal and nearshore environments, which can be used to test hypotheses concerning future changes associated with climate change and ocean acidification along the Pacific Coast of North America.

Local adaptation of sex induction in a facultative sexual crustacean: insights from QTL mapping and natural populations of D aphnia magna - Anne C. Roulin; Jarkko Routtu; Matthew D. Hall; Tim Janicke; Isabelle Colson; Christoph R. Haag; Dieter Ebert (Molecular Ecology, 2013)
Dormancy is a common adaptation in invertebrates to survive harsh conditions. Triggered by environmental cues, populations produce resting eggs that allow them to survive temporally unsuitable conditions. D aphnia magna is a crustacean that reproduces by cyclical parthenogenesis, alternating between the production of asexual offspring and the sexual reproduction of diapausing eggs (ephippia). Prior to ephippia production, males (necessary to ensure ephippia fertilization) are produced parthenogenetically. Both the production of ephippia and the parthenogenetic production of males are induced by environmental factors. Here, we test the hypothesis that the induction of D . magna resting egg production shows a signature of local adaptation. We postulated that D aphni a from permanent ponds would produce fewer ephippia and males than D aphnia from intermittent ponds and that the frequency and season of habitat deterioration would correlate with the timing and amount of male and ephippia production. To test this, we quantified the production of males and ephippia in clonal D . magna populations in several different controlled environments. We found that the production of both ephippia and males varies strongly among populations in a way that suggests local adaptation. By performing quantitative trait locus mapping with parent clones from contrasting pond environments, we identified nonoverlapping genomic regions associated with male and ephippia production. As the traits are influenced by two different genomic regions, and both are necessary for successful resting egg production, we suggest that the genes for their induction co‐evolve.

Interactions between environmental stressors: the influence of salinity on host–parasite interactions between Daphnia magna and Pasteuria ramosa - Matthew D. Hall; Andrea Vettiger; Dieter Ebert (Oecologia, 2013)

Development of best practices for ex situ conservation of radish germplasm in the context of the crop genebank knowledge base - I. Thormann; Q. Yang; C. Allender; N. Bas; G. Campbell; M. E. Dulloo; A. W. Ebert; U. Lohwasser; C. Pandey; L. D. Robertson; O. Spellman (Genetic Resources and Crop Evolution, 2013)

A novel approach to parasite population genetics: Experimental infection reveals geographic differentiation, recombination and host‐mediated population structure in P asteuria ramosa , a bacterial parasite of D aphnia - J. P. Andras; D. Ebert (Molecular Ecology, 2013)
The population structure of parasites is central to the ecology and evolution of host‐parasite systems. Here, we investigate the population genetics of P asteuria ramosa , a bacterial parasite of D aphnia . We used natural P . ramosa spore banks from the sediments of two geographically well‐separated ponds to experimentally infect a panel of D aphnia magna host clones whose resistance phenotypes were previously known. In this way, we were able to assess the population structure of P . ramosa based on geography, host resistance phenotype and host genotype. Overall, genetic diversity of P . ramosa was high, and nearly all infected D . magna hosted more than one parasite haplotype. On the basis of the observation of recombinant haplotypes and relatively low levels of linkage disequilibrium, we conclude that P . ramosa engages in substantial recombination. Isolates were strongly differentiated by pond, indicating that gene flow is spatially restricted. P asteuria ramosa isolates within one pond were segregated completely based on the resistance phenotype of the host—a result that, to our knowledge, has not been previously reported for a nonhuman parasite. To assess the comparability of experimental infections with natural P . ramosa isolates, we examined the population structure of naturally infected D . magna native to one of the two source ponds. We found that experimental and natural infections of the same host resistance phenotype from the same source pond were indistinguishable, indicating that experimental infections provide a means to representatively sample the diversity of P . ramosa while reducing the sampling bias often associated with studies of parasite epidemics. These results expand our knowledge of this model parasite, provide important context for the large existing body of research on this system and will guide the design of future studies of this host‐parasite system.

New eastern Pacific Ocean records of Hydrolagus melanophasma , with annotations of a juvenile female - H. Aguirre‐Villaseñor; C. Salas‐Singh; J. Madrid‐Vera; J. Martínez‐Ortiz; D. A. Didier; D. A. Ebert (Journal of Fish Biology, 2013)
Two new records of Hydrolagus melanophasma , one juvenile female from off the central Mexican coast and one adult male from off the coast of Ecuador, confirm the presence of this species throughout its known range in the eastern Pacific Ocean, from southern California, U.S.A., to Valdivia, Chile. This report gives a description and comparison of proportional measurements, head shape and colouration for juvenile and adult H. melanophasma . A taxonomic key to distinguish the eastern Pacific Ocean species of Hydrolagus is included.

Evidence of stability in a chondrichthyan population: case study of the spotted ratfish Hydrolagus colliei (Chondrichthyes: Chimaeridae) - L. A. K. Barnett; D. A. Ebert; G. M. Cailliet (Journal of Fish Biology, 2012)
Results presented here provide evidence of an exception to the generalization that all chondrichthyan populations are especially vulnerable to exploitation to the extent that they remain at low abundance for a protracted or indefinite duration even after exploitation rates are reduced. Delta log‐normal generalized linear models (GLM) and cluster analysis of fishery‐independent catch‐per‐unit‐effort (CPUE) data from 1977 to 2006 indicated the presence of at least two distinct stocks of spotted ratfish Hydrolagus colliei off the U.S. West Coast. CPUE of the continental slope and northern continental shelf and upper slope populations did not vary between 1977 and 1995 and increased from 1995 to 2006. On the basis of the timing of these changes, it is likely that both fishing and climate influenced these trends. Sex and size‐specific differences in bathymetric distribution, along with the identification of nursery sites, indicate that fishery by‐catch could have a significant effect on population growth. These aggregative behaviours, combined with low fecundity, indicate that H. colliei may be vulnerable to irreversible population depletion by fisheries mortality. Temporal abundance trends indicated, however, that their population size has increased significantly within the last decade, a demonstration of population stability. A literature review indicated that there is also evidence for population stability in other chondrichthyans. The paradigm that all chondrichthyan populations fail to rebuild in response to exploitation, therefore, may not be as broadly applicable as previously thought. Thus, it is not necessarily sufficient to make generalizations regarding the vulnerability of chondrichthyans across higher taxonomic scales.

Stable‐isotope analysis of a deep‐sea benthic‐fish assemblage: evidence of an enriched benthic food web - M. D. Boyle; D. A. Ebert; G. M. Cailliet (Journal of Fish Biology, 2012)
In this study, fishes and invertebrates collected from the continental slope (1000 m) of the eastern North Pacific Ocean were analysed using stable‐isotope analysis (SIA). Resulting trophic positions ( T P ) were compared to known diets and habitats from the literature. Dual isotope plots indicated that most species groups (invertebrates and fishes) sorted as expected along the carbon and nitrogen axes, with less intraspecific variability than interspecific variability. Results also indicated an isotopically distinct benthic and pelagic food web, as the benthic food web was more enriched in both nitrogen and carbon isotopes. Trophic positions from SIA supported this finding, resulting in the assignment of fishes to different trophic positions from those expected based on published dietary information. These differences can be explained largely by the habitat of the prey and the percentage of the diet that was scavenged. A mixing model estimated dietary contributions of prey similar to those of the known diet of Bathyraja trachura from stomach‐content analysis (SCA). Linear regressions indicated that trophic positions calculated from SIA and SCA, when plotted against B. trachura total length for 32 individuals, exhibited similar variation and patterns. Only the T P from SCA yielded significant results (stomach content: P P > 0·05).

An overview on the role of Hexanchiformes in marine ecosystems: biology, ecology and conservation status of a primitive order of modern sharks - A. Barnett; J. M. Braccini; C. A. Awruch; D. A. Ebert (Journal of Fish Biology, 2012)
The large size, high trophic level and wide distribution of Hexanchiformes (cow and frilled sharks) should position this order as important apex predators in coastal and deep‐water ecosystems. This review synthesizes available information on Hexanchiformes, including information not yet published, with the purpose of evaluating their conservation status and assessing their ecological roles in the dynamics of marine ecosystems. Comprising six species, this group has a wide global distribution, with members occurring from shallow coastal areas to depths of c. 2500 m. The limited information available on their reproductive biology suggests that they could be vulnerable to overexploitation ( e.g. small litter sizes for most species and suspected long gestation periods). Most of the fishing pressure exerted on Hexanchiformes is in the form of commercial by‐catch or recreational fishing. Comprehensive stock and impact assessments are unavailable for most species in most regions due to limited information on life history and catch and abundance time series. When hexanchiform species have been commercially harvested, however, they have been unable to sustain targeted fisheries for long periods. The potentially high vulnerability to intense fishing pressure warrants a conservative exploitation of this order until thorough quantitative assessments are conducted. At least some species have been shown to be significant apex predators in the systems they inhabit. Should Hexanchiformes be removed from coastal and deep‐water systems, the lack of sympatric shark species that share the same resources suggests no other species would be capable of fulfilling their apex predator role in the short term. This has potential ecosystem consequences such as meso‐predator release or trophic cascades. This review proposes some hypotheses on the ecology of Hexanchiformes and their role in ecosystem dynamics, highlighting the areas where critical information is required to stimulate research directions.

Transgenerational effects of poor elemental food quality on Daphnia magna - Paul C. Frost; Dieter Ebert; James H. Larson; Michelle A. Marcus; Nicole D. Wagner; Alexandra Zalewski (Oecologia, 2010)

Assessment of the dorsal fin spine for chimaeroid (Holocephali: Chimaeriformes) age estimation - L. A. K. Barnett; D. A. Ebert; G. M. Cailliet (Journal of Fish Biology, 2009)
Previous attempts to age chimaeroids have not rigorously tested assumptions of dorsal fin spine growth dynamics. Here, novel imaging and data‐analysis techniques revealed that the dorsal fin spine of the spotted ratfish Hydrolagus colliei is an unreliable structure for age estimation. Variation among individuals in the relationship between spine width and distance from the spine tip indicated that the technique of transverse sectioning may impart imprecision and bias to age estimates. The number of growth‐band pairs observed by light microscopy in the inner dentine layer was not a good predictor of body size. Mineral density gradients, indicative of growth zones, were absent in the dorsal fin spine of H. colliei , decreasing the likelihood that the bands observed by light microscopy represent a record of growth with consistent periodicity. These results indicate that the hypothesis of aseasonal growth remains plausible and it should not be assumed that chimaeroid age is quantifiable by standard techniques.

Comparative feeding ecology of four sympatric skate species off central California, USA - J. J. Bizzarro; H. J. Robinson; C. S. Rinewalt; D. A. Ebert (Environmental Biology of Fishes, 2009)

Variable-Number-of-Tandem-Repeats Analysis of Genetic Diversity in Pasteuria ramosa - L. Mouton; D. Ebert (Current Microbiology, 2008)

Level ground and uphill cycling ability in elite female mountain bikers and road cyclists - F. M. Impellizzeri; T. Ebert; A. Sassi; P. Menaspà; E. Rampinini; D. T. Martin (European Journal of Applied Physiology, 2007)

Age and growth of the roughtail skate Bathyraja trachura (Gilbert 1892) from the eastern North Pacific - Chanté D. Davis; Gregor M. Cailliet; David A. Ebert (Environmental Biology of Fishes, 2007)

Galantamine: a cholinergic patch in the treatment of alcoholism: a randomized, placebo-controlled trial - K. Mann; K. Ackermann; A. Diehl; D. Ebert; G. Mundle; H. Nakovics; T. Reker; G. Richter; L. G. Schmidt; M. Driessen; K. Rettig; K. Opitz; et al. (Psychopharmacology, 2006)

Linking Land Cover and Water Quality in New York City’S Water Supply Watersheds - M. H. Mehaffey; M. S. Nash; T. G. Wade; D. W. Ebert; K. B. Jones; A. Rager (Environmental Monitoring and Assessment, 2005)

Reproductive biology of skates, Bathyraja (Ishiyama), along the eastern Bering Sea continental slope - D. A. Ebert (Journal of Fish Biology, 2005)
Eight Bathyraja skate species, Bathyraja aleutica , Bathyraja interrupta , Bathyraja lindbergi , Bathyraja maculata , Bathyraja minispinosa , Bathyraja parmifera , Bathyraja taranetzi and Bathyraja trachura , collected along the eastern Bering Sea continental slope were examined for reproductive features. The sex ratio for six of eight Bathyraja skate species studied was c . 1 : 1 with males dominating for B. interrupta and B. parmifera . Five of eight species examined, B. aleutica , B. lindbergi , B. parmifera , B. taranetzi and B. trachura approximately equalled or exceeded the maximum reported total length, L T . Maximum L T for three species ( B. interrupta , B. minispinosa and B. parmifera ) revealed that the largest individuals were males and that in three other species ( B. lindbergi , B. maculata and B. trachura ) both females and males grew to approximately the same size. Both females and males matured at approximately the same L T for seven of eight species. Only female B. aleutica matured at a much larger size than males. All species matured within a narrow size range following a protracted juvenile stage and once mature these skates appeared to grow very little. First maturity for all species occurred at ≥80% of their maximum L T . The number of oocytes did not significantly differ between the left and right ovary for any species. The total number of mature oocytes increased with L T for six of eight species examined. The number of oocytes for one species, B. aleutica , increased in number until 145 cm L T , then declined in those individuals greater in length. The egg cases of all species are described, of which four ( B. lindbergi , B. parmifera , B. taranetzi and B. trachura ) have never been previously reported. Evidence is presented that suggest skates may be limited to as little as one and as many as 13 spawning seasons, depending on the species, and that senescence may occur in older individuals.

Prefrontal cortical hypometabolism during low-dose interferon alpha treatment - Freimut D. Juengling; Dieter Ebert; Oliver Gut; Marc A. Engelbrecht; J. Rasenack; Egbert U. Nitzsche; Joachim Bauer; Klaus Lieb (Psychopharmacology, 2000)

Assessing Landscape Condition Relative to Water Resources in the Western United States: A Strategic Approach - K. Bruce Jones; Daniel T. Heggem; Timothy G. Wade; Anne C. Neale; Donald W. Ebert; Maliha S. Nash; Megan H. Mehaffey; Karl A. Hermann; Anthony R. Selle; Scott Augustine; Iris A. Goodman; Joel Pedersen; et al. (Environmental Monitoring and Assessment, 2000)

Hepatitis E virus infection in chimpanzees: a retrospective analysis - K. A. McCaustland; K. Krawczynski; J. W. Ebert; M. S. Balayan; A. G. Andjaparidze; J. E. Spelbring; E. H. Cook; C. Humphrey; P. O. Yarbough; M. O. Favorov; D. Carson; D. W. Bradley; et al. (Archives of Virology, 2000)

Abundance, distribution, morphometrics, reproduction and diet of the Izak catshark - A. J. Richardson; G. Maharaj; L. J. V. Compagno; R. W. Leslie; D. A. Ebert; M. J. Gibbons (Journal of Fish Biology, 2000)
Holohalaelurus regani was caught in 38% of the 3314 bottom trawls conducted during routine demersal surveys o. the South African west and south coasts from 1986 to 1999. An index of biomass for H. regani has increased on the west coast, from 1606 t in 1986–1993 to 3012 t in 1994–1999, despite c. 130 t being taken annually as by–catch in the demersal fishery. On the south coast, there has also been an increase over the same period, from 793 to 1350 t. Females and juveniles were generally found in shallower water ( H. regani become mature at 450–500 mm LT, whereas females become mature at 400–450 mm LT. There is reproductive activity throughout the year and fecundity appears to be high. This species is a generalist feeder, with the diet comprising teleosts, crustaceans and cephalopods. H. regani also scavenges offal opportunistically. Its high fecundity, the relative protection of females and juveniles in shallow water that is rarely trawled, its opportunistic diet and its robust nature that may allow it to survive after it has been discarded, have enabled H. regani to increase in numbers, despite indirect fishing pressure.

Biorecognition of HPMA Copolymer-Adriamycin Conjugates by Lymphocytes Mediated by Synthetic Receptor Binding Epitopes - Vladimir Omelyanenko; Pavla Kopečková; Ramesh K. Prakash; Charles D. Ebert; Jindřich Kopeček (Pharmaceutical Research, 1999)

Neurobiological similarities in antidepressant sleep deprivation and psychostimulant use: a psychostimulant theory of antidepressant sleep deprivation - D. Ebert; Mathias Berger (Psychopharmacology, 1998)

Einfluß zentralnervöser koordination im Sinne v. HOLSTs auf die Steuerung von Atem- und Extremitätenmotorik des Menschen - B. Raßler; S. Waurick; D. Ebert (Biological Cybernetics, 1990)